Odpowiedzi

2009-09-10T17:59:07+02:00
Mnozenie to wielokrotne dodawanie
2⁵ + 2⁵ = 2⁶
2*2⁵=2₆

(-3)³ + (-3)³ + (-3)³ = -3⁴
(-3)³ + (-3)³ + (-3)³=3*(-3)³ ale (-3)³=-(3)³
3*(-3)³ =-3*3³=-3⁴

Pozdr

Hans
5 2 5
2009-09-10T18:08:02+02:00
A) 2⁵ + 2⁵ = 2⁶
2⁵ = 32
2⁶ = 64

2⁵ + 2⁵ = 2⁶
32 + 32 = 64

b) (-3)³ + (-3)³ + (-3)³ = -3⁴
(-3)³ = -27

-3⁴ = -81
(-3)³ + (-3)³ + (-3)³ = -3⁴
(-27) + (-27) + (-27) = -81
9 4 9
Najlepsza Odpowiedź!
  • Użytkownik Zadane
2009-09-10T18:17:03+02:00
2⁵ + 2⁵ = 2*2⁵ = 2¹*2⁵=2⁶

(-3)³ + (-3)³ + (-3)³ = 3*(-3)³=3¹*(-3)³=-3⁴
9 4 9